Organic composition of carbonaceous aerosols in an aged prescribed fire plume - B Yan; M* Zheng; YT Hu; S* Lee; Kim HK; Russell AG (Atmos. Chem. Phys., 2008)
For the time being, Integrated Optics is able to produce a range of devices able of efficiently modulating phase, amplitude and frequency of guided waves in single mode structures implemented at the surface of active materials such as Lithium Niobate. In most of the cases, their basic principle relies on the interference pattern of two guided waves and the classical implementations of such modulators were mainly related to COBRA switch type directional couplers or to MACH ZEHNDER type interferometers. Only very recently a structure combining the coupled waveguides of a COBRA and the Y junction of the MACH ZEHNDER interferometer was designed. This paper is an analysis of the switching characteristics of this Y-fed directional coupler and of its high frequency modulation properties.